Islamic Banking in Lebanon: Challenges and Opportunities - MERHI, FIRAS (2012)
Islamic finance and banking have witnessed tremendous growth globally. It isn’t limited to Islamic countries anymore, where Western countries started welcoming this new industry. Despite all this growth development and success Islamic banking is achieving worldwide, this industry hasn’t yet shown a significant in the Lebanese Market. This paper aims to find the reasons behind the lack of growth of Islamic banking practices in Lebanon. Moreover it will try to spot opportunities present for this industry.